Texas Water Agency Poised to Sell $90 Million in Debt - Albanese, Elizabeth (The Bond buyer (New York, N.Y. 1982), 2005)
Warren Brewer, the authority's Northern Region manager, said the TRA hopes to realize a present value savings of 3% on the callable bonds in its Series 1999 and 2003 issues. "We will be watching the market carefully," he said. "But we believe the market will provide for present value savings in excess of the 3% target, and while we could refund the debt whether or not it hits that target, management has recommended to our five member cities that they accept the 3% target. Depending on the market at the time of sale, we could shift the refunding amount." The bonds will be insured by MBIA Insurance Corp. The authority's debt carries underlying ratings of A from Standard & Poor's and A1 from Moody's Investors Service, the only two agencies to rate the bonds. The bonds are currently structured as serials running through 2025, although that composition is subject to change, dependent upon market demand, Brewer said. The authority provides water to five member cities -- Euless, Grapevine, Bedford, North Richland Hills, and Colleyville -- through a contract with the Tarrant Regional Water District. The contract's life matches that of the authority's outstanding debt.